Experimental Study on the Optimization of Polymer-Modified Cement-Based Composite Sealing Materials and Mechanical Properties and Permeability of Cemented Coal Bodies - Zhang, Baoyong; Yu, Yue; Gao, Xia; Wu, Qiang; Zhang, Qiang; Liu, Chuanhai (Frontiers in Materials, 2022)
As a critical technical issue, gas extraction borehole sealing significantly restricts the effects of gas extraction. Polymer modified cement-based composite (PMCC) sealing materials were developed to improve the sealing effect of gas extraction drilling. In this study, a self-built mechanical property and permeability test platform for grouting-based cemented coal bodies was used to test the viscosity, gelation time, and mechanical properties of PMCC sealing materials and the permeability of cemented coal bodies. Through the obtained relevant results, it was demonstrated that the material viscosity of PMCC sealing materials and the permeability and compressive strength of cemented bodies are under the influence of additive ratios. Moreover, the viscosity of sealing materials was found to be linearly related to the gelation time. In particular, the higher the viscosity, the shorter the gelation time. Additionally, on one hand, it was found that the viscosity of such sealing materials is positively correlated to the compressive strength of cemented coal bodies. On the other hand, it forms a negative correlation with their permeability. Based on relevant analysis outcomes, it was deemed that the sufficient hydration reaction and the interspace reticulate microstructure formed by the polymer of PMCC sealing materials allow the cemented coal body to achieve high compressive strength and low permeability.